Increased severity of respiratory syncytial virus airway infection due to passive smoke exposure. Issue 9 (30th July 2018) - Maedel, Clemens; Kainz, Katharina; Frischer, Thomas; Reinweber, Matthias; Zacharasiewicz, Angela
Abstract: Objective: Aim of this study was to analyze whether children with objectively measured second‐hand cigarette smoke (SHS) exposure suffer from a more severe course of disease when hospitalized with lower respiratory tract infection (LRTI) due to respiratory syncytial virus (RSV). Methods: This prospective study was conducted at the Department of Pediatrics, Wilhelminen‐Hospital, Vienna, Austria in children aged below 1 year without a history of preceding lung disease and with acute symptoms of LRTI and a positive nasopharyngeal swab for RSV. On admission, urinary cotinine was measured as a marker of recent SHS and clinical severity of LRTI was assessed by oxygen saturation SpO2 and the "admission clinical severity score" (CSSA). Parents/caregivers were asked to complete a customized questionnaire assessing risks for SHS and demographic characteristics. Results: After inclusion of 217 patients, data of 185 patients with a mean (SD) age of 106 days (80) were analyzed. Twenty‐five patients (13.5%) were "cotinine‐positive" (COT+) defined as a urinary cotinine level of ≥7 μg/L. SpO2 on admission was significantly lower in children recently exposed to SHS defined objectively by COT+ (94.8%  ±2.0) in urine on admission compared to children not recently exposed (COT−) (96.8% ±3.0; P  < 0.01). Disease severity, assessed via mean clinical severity score on admission (CSSA) for COT+ and COT− was 2.56 and 1.71, respectively ( P  = 0.03). Conclusions: Recent exposure to SHS was associated with lower O2 saturation and higher clinical severity score, measured by urine cotinine levels in children hospitalized for RSV infection under 1 year of age.